Replication Data for: Adequate vegetative cover decreases nitrous oxide emissions from cattle urine deposited in grazed pastures under rainy season conditions - Chirinda, Ngonidzashe; Loaiza, Sandra; Arenas Calle, Laura N.; Ruíz, Verónica; Faverín, Claudia; Álvarez, Carolina; Savian, Jean Víctor; Belfon, Renaldo; Zuñiga, Karen; Morales, Luis; Trujillo, Catalina; Arango, Miguel; et al. (International Center for Tropical Agriculture, 2018)
The new Latin America Greenhouse Gas Mitigation Network (LAMNET) is a regional subsidiary of The Climate Food and Farming Research Network (CLIFF), an international research network that helps to build the capacity of young researchers working on climate change mitigation in smallholder farming. The objective of the network is to enhance regional capacity to conduct mitigation research. Experiments at seven sites in five countries of LAC region compared emissions from paired pastures with low vegetative cover and adequate vegetative cover based on a combination of estimates of aboveground biomass and local farmer assessments. Were quantified N2O emissions from simulated cattle urine patches with closed static chamber methodology. • Major variables: Urine content (Kg N ha-1), Daily flux (mg N2O m-2 d-1), Accumulated fluxes (Kg N _ N2O ha-1), Emission factor _ urine.